Mastering knife skills - Russo, Denise (New York Larsen & Keller, 2017)
The proper use of a knife is very important in the culinary arts. Uniform cooking of dishes as well as the release of flavors require proper cutting of ingredients. Different cutting techniques include the chop, the dice, the slice and cut, chiffonade and julienne. Certain food preparations require specific techniques of cutting ingredients as well as specifically designed knives. This book, with its detailed data, will prove immensely beneficial to professionals and students involved in this area. The extensive contents of this book provide the readers with a thorough understanding of this craft.--Provided by publisher.
Includes index.
Keywords: Knives; Cutting